Patterns of Self-Medication and Drug Storage: A Global Meta-Analysis: Self-medication and drug storage: a global meta-analysis - Sahebi, Leyla; Abouhamzeh, Kosar; Sahebi, Roya (Iranian Journal of Pharmaceutical Sciences, 2023)
Self-medication, a universal public health issue, is an increasingly common concern. A meta-analysis of global self-medication patterns will be worthwhile for a comprehensive yet comparative consideration of the burden and related problems and planning for macro-health interventions and policies. This study aimed to determine the patterns of self-medication and drug storage behavior globally in various subgroups and its related factors. A systematic search detected relevant studies (1995 to 2018) in the English databases. The related observational study was concluded in this study. Studies that examined self-medication and drug storage at home in the general population were entered into the study. The pooled proportion and odds ratio of self-medication and drug storage at home were calculated by STATA -14. Of 25’225 titles found, 95 studies were included in the final analysis. The pooled prevalence of self-medication was calculated at 54.0% ±4.0% (60% for over-the-counter (OTC) drugs and 43.0% for prescription-only medicines (POM) drugs). The pooled prevalence of drug storage at home was estimated to be 53.0% (CI 95%: 36.0, 70.0). The proportion of self-medication and drug storage at home in continents was: Africa 64.0% and 39.0%, Asia 58.0% and 64.0%, Europe 39.0% (both), and America 32.0% and 8.0%, respectively. African countries had the highest consumers of POM drugs as well as antibiotics. Pharmacists provided the most information about drugs in African studies. The adjusted odds ratio of self-medication was higher in females with higher education status in European and African countries. The prevalence of self-medication for POM drugs was noteworthy, especially in Asian and African countries. Comprehensive education for pharmacists must be accomplished. Also, increasing drug information is critical for women who usually manage family health in households.